Highly adjustable piezoelectric properties in two-dimensional LiAlTe2 by strain and stacking. (8th November 2021) - Qiu, Jian; Chen, Xianping; Zhang, Fusheng; Zhu, Bao; Guo, Haojie; Liu, Xiaodong; Yu, Jiabing; Bao, Jiading
Abstract: Two-dimensional (2D) piezoelectric materials have attracted wide attention because they are of great significance to the composition of piezoelectric nanogenerators. In this work, we have systematically studied the piezoelectric properties of 2D LiAlTe2 by using the first-principles calculation and found the 2D LiAlTe2 monolayer exhibits both large in-plane piezoelectric coefficient d 11 (3.73 pm V −1 ) and out-of-plane piezoelectric coefficient d 31 (0.97 pm V −1 ). Moreover, the piezoelectric coefficients of 2D LiAlTe2 are highly tunable by strain and stacking. When different uniaxial strains are applied, d 11 changes dramatically, but d 31 changes little. When 2% stretching is applied to 2D LiAlTe2 monolayer along the x -axis, d 11 reaches 7.80 pm V −1, which is twice as large as the previously reported 2D piezoelectric material MoS2 . Both AA stacking and AB stacking can enhance the piezoelectric properties of 2D LiAlTe2, but they have different effects on in-plane and out-of-plane piezoelectric coefficients. AA stacking can greatly increase d 31 but has little impact on d 11 . In the case of four-layer AA stacking, the d 31 reaches 3.32 pm V −1 . AB stacking can both increase d 11 and d 31, but d 11 grows faster than d 31 as the number of layers increases. In the case of four-layer AB stacking, d 11 reaches 18.05 pm V −1 . The excellent and highly tunable piezoelectric performance provides 2D LiAlTe2 greater potential for the application of piezoelectric nano-generators and other micro-nano piezoelectric devices.